Estado de la investigación primatológica en el Eje Cafetero y Antioquia, Colombia - García-R, Sebastián; Montilla, Sebastián O.; Manrique, Vanessa Bustamante; Manrique, Sebastián Bustamante; Cepeda-Duque, Camilo; Londoño, Juan David Sánchez; Ramírez-Chaves, Héctor E. (Neotropical Primates, 2018)
The Tropical Andes Hotspot is a high conservation priority. A high proportion of the northern Colombian Andes has been deforested affecting its biological diversity, including primates, for which there are information gaps that hinder the formulation of conservation strategies. We conducted a bibliographic search on studies of non-human primates developed in the northern portion of the Central and Western cordilleras, to generate a baseline facilitating the priorization of information generation and guidelines to formulate research projects at the regional level. We updated the species list for the fourth departments evaluated, recording a total of 13 species (Antioquia: 13; Caldas: 6; Risaralda: 5; Quindío: 2). We compiled a total of 120 studies which evidenced a greater research effort in topics related to ecology, genetics, and veterinary medicine, as well as a reduced emphasis in ethnobiological research. Saguinus leucopus and Alouatta seniculus were the most studied species, contrasting with the scarce information generated for threatened species such as Ateles fusciceps, Ateles hybridus, three especies of Aotus (lemurinus, zonalis, griseimembra), Alouatta palliata, Cebus versicolor, Lagothrix lagotricha, Saguinus geoffroyi and Saguinus oedipus.